2009
DOI: 10.1002/hec.1422
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of two healthcare costing methods: bottom‐up and top‐down

Abstract: This paper compares two quite different approaches to estimating costs: a 'bottom-up' approach, represented by the US Department of Veterans Affairs' (VA) Decision Support System that uses local costs of specific inputs; and a 'top-down' approach, represented by the costing system created by the VA Health Economics Resource Center, which assigns the VA national healthcare budget to specific products using various weighting systems. Total annual costs per patient plus the cost for specific services (e.g. clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
201
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 211 publications
(211 citation statements)
references
References 25 publications
6
201
1
3
Order By: Relevance
“…23 Other studies have demonstrated that the difference can be as high as 20%. 27 The bottom-up approach is more accurate because it allocates costs based on the actual consumption of specific resources, especially those relating to administrative and other services that support patient care. These represent a significant proportion of total direct costs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Other studies have demonstrated that the difference can be as high as 20%. 27 The bottom-up approach is more accurate because it allocates costs based on the actual consumption of specific resources, especially those relating to administrative and other services that support patient care. These represent a significant proportion of total direct costs.…”
Section: Methodsmentioning
confidence: 99%
“…These represent a significant proportion of total direct costs. 27 In general, three types of costs need to be considered: direct costs, which include hospitalisation costs, physicians costs and medication costs; indirect costs, which are those borne by the patient (eg as time off work, time of travel and productivity losses); and opportunity costs. 28,29 An opportunity cost is the cost incurred because a limited resource is being used to treat a preventable pathology.…”
Section: Methodsmentioning
confidence: 99%
“…Second, there is the potential for variation in attributing specific costs to a cost center across VA medical centers. 42 However, total costs should not be influenced by variation in attribution to cost centers because the VA has a national costing system. In addition, we have previously demonstrated a strong correlation (r=0.87) between use and costs.…”
Section: Discussionmentioning
confidence: 99%
“…We used the method created by Yu et al [18] and Phibbs et al [19] to categorize these codes into primary care and internal medicine, psychiatry and substance use, rehabilitation, and other services (e.g., ancillary, diagnostic, prosthetic, dental, nursing home, and home care). We used Health Economics Resource Center (HERC) Average Cost data instead of Decision Support System data; the two sources are highly correlated when annualized, and HERC provides an annualized data set that is easy to use [20]. We extracted data for fiscal years 2002 to 2007, resulting in a median of 6 years (range: 4-6) of data per patient.…”
Section: Methodsmentioning
confidence: 99%